2002
DOI: 10.1006/aima.2001.2060
|View full text |Cite
|
Sign up to set email alerts
|

Integral Representations of Solutions of Differential Equations Free from Accessory Parameters

Abstract: We show that every accessory parameter free system of differential equations of Okubo normal form has integral representation of solutions. The proof is constructive; we study the change of solutions under the operations}the extension and the restriction, which have been introduced by Yokoyama [Construction of systems of differential equations of Okubo normal form with rigid monodromy, preprint] in order to construct every such system of differential equations. Several examples are given. # 2002 Elsevier Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Our method follows from the construction of Fuchsian systems of differential equations with monodromy representations corresponding to rigid local systems of semi-simple type, which give an explicit solution of the Riemann-Hilbert problem for such representations (Proposition 1.2 and Theorem 1.6). Moreover by applying the result in [6] we show that such Fuchsian systems of differential equations have integral representations of the solutions (Theorem 3.2). In terms of local systems, this result means that every section of every rigid local system of semi-simple type has an integral representation.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Our method follows from the construction of Fuchsian systems of differential equations with monodromy representations corresponding to rigid local systems of semi-simple type, which give an explicit solution of the Riemann-Hilbert problem for such representations (Proposition 1.2 and Theorem 1.6). Moreover by applying the result in [6] we show that such Fuchsian systems of differential equations have integral representations of the solutions (Theorem 3.2). In terms of local systems, this result means that every section of every rigid local system of semi-simple type has an integral representation.…”
Section: Introductionmentioning
confidence: 93%
“…In [6] we have shown that every irreducible rigid system of ONF of semi-simple type has an integral representation of the solutions of Euler type. Suppose that the system (1.3) is irreducible, rigid and of semi-simple type.…”
Section: Integral Representationsmentioning
confidence: 98%
See 3 more Smart Citations